A randomized controlled trial of social cognition and interaction training for persons with first episode psychosis in Hong Kong - Lo, Panmi M. T.; Lui, Simon S. Y.; Law, Colin K. M.; Roberts, David L.; Siu, Andrew M. H. (Frontiers in Psychiatry, 2023)
Social cognitive impairment is a core limiting factor of functional recovery among persons with first episode psychosis (FEP). Social Cognition and Interaction Training (SCIT) is a group-based, manualized training with demonstrated evidence in improving social cognitive performance among people with schizophrenia. However, there are few studies on the effect of SCIT for people with FEP and for people in non-Western societies. This study evaluated the feasibility, acceptability and initial effectiveness of the locally-adapted SCIT in improving social cognitive functioning in Chinese people with FEP. The SCIT was delivered two sessions per week over a 10-weeks period, each session lasted for 60-90 min. A total of 72 subjects with FEP were recruited from an outpatient clinic and randomized to conventional rehabilitation (“Rehab”) and experimental (“SCIT and Rehab”) groups. Primary outcome measures included four social cognitive domains including emotion perception, theory-of-mind, attributional bias and jumping-to-conclusion, and secondary measures included neurocognition, social competence and quality of life. Participants were assessed at baseline, post-treatment, and 3-months post-treatment. Repeated measures ANCOVAs, with baseline scores as covariates, were used to compare the group differences in various outcomes across time. The results showed that the SCIT was well-accepted, with a satisfactory completion rate and subjective ratings of relevance in the experimental group. Moreover, treatment completers (n = 28) showed evidence of an advantage, over conventional group (n = 31), in reduced attributional bias and jumping-to-conclusions at treatment completion, lending initial support for the SCIT in Chinese people with FEP. Future research should address the limitations of this study, using more refined outcome measurements and higher treatment intensity of the SCIT.